Effects of ammonia toxicity on growth performance, cortisol, glucose and hematological response of Nile Tilapia (Oreochromis niloticus) - Moustafa M. Zeitoun; Kheir El-Din M. EL-Azrak; Mohamed A. Zaki; Bahig R. Nemat-Allah; El-Sayed E. Mehana (Syiah Kuala University, 2016)
Ammonia is a production limiting factor in the aquaculture media affecting fish production. A study was designed to scrutinize effects of ammonia on growth performance, survival, cortisol and hematological parameters of Tilapia fish. The study examined effects of 96 h-incubation of male and female Tilapia with 3 mg ammonium chloride per a liter of water compared to control. The study has been carried out in the physiology laboratory of the department of animal and fish production, Alexandria University. Fourteen aquaria were used (6 control and 8 ammoniated). Each aquarium contained 6 fish (half the population males and the other have females). Duration of the control reared fish was 30 days, however the duration for ammoniated group was 4 days. In all stressed fish, there found decreases in final body weight, average daily gain and specific growth rate as compared to controls. Hematological parameters revealed increases (P0.05) in total leukocyte counts in both males and females exposed to stressors. There were significant decreases (P0.05) in red blood cell, hematocrit value and hemoglobin concentration in both males and females. There were non-significant differences (P0.10) in these parameters between males and females. Exposing both male and female tilapia to ammonia, resulted in increases (P0.05) in mean corpuscular volume (MCV). Mean corpuscular hemoglobin (MCH) didn’t change in male tilapia, while females expressed increased MCH values in the ammonia condition. Mean corpuscular hemoglobin concentration (MCHC) decreased (P0.05) under ammonia with no differences between males and females. Differential leukocyte count exhibited increases (P0.05) in neutrophils in ammonia-exposed males and females and decreases (P0.05) in eosinophils and monocytes in males, but not in females. However, lymphocytes decreased (P0.05) in both females and males exposed to ammonia. Cortisol level increased (P0.05) by about 2 folds in both sexes of fish exposed to ammonia (2.95 and 2.72 vs6.40 and 6.48 ng/ml in control males and females vs ammonia-exposed males and females).Rearing tilapia fish in media containing high level (3mg/l water) of ammonium chloride not only deteriorated growth rate but it also negatively affected the health wellbeing.